Breeding of zebrafish in the laboratory environment for research development - Sang Ho Kim; Chanchal Sharma; Imran Khan; Sun Chul Kang (Bangladesh Pharmacological Society, 2017)
The zebrafish (Danio rerio) has turn out to be an excellent vertebrate organism for analyzing developmental stages, disease modeling, and screening of drug toxicities due to their minuscule, high fecundity, optical transparency and there close parallels with the genome of human beings. Although maintenance of zebrafish is relatively easy, yet it is a complex process, greatly influenced by various factors including mating behavior, day-light cycle, age, and size of fish. This visual experiment will provide an overview of zebrafish care and maintenance in the laboratory environment. Additionally, the presentation will include information essential for improving the spawning habitat by recreating breeding settings in the lab. Collectively, this experimental memorandum of zebrafish environment can serve as a mean to understand the reproducibility, efficiency of use and its welfare for future research development. Video Clip of Methodology: 2 min 52 sec:   Full Screen   Alternate